Identifying Social Care Research Literature: Case Studies From Guideline Development - Stansfield, Claire; Liabo, Kristin (Evidence Based Library and Information Practice, 2017)
Objective – Systematic searching is central to guideline development, yet guidelines in social care present a challenge to systematic searching because they exist within a highly complex policy and service environment. The objective of this study was to highlight challenges and inform practice on identifying social care research literature, drawing on experiences from guideline development in social care.Methods – The researchers reflected on the approaches to searching for research evidence to inform three guidelines. They evaluated the utility of major topic-focused bibliographic database sources through a) determining the yield of citations from the search strategies for two guidelines and b) identifying which databases contain the citations for three guidelines. The researchers also considered the proportion of different study types and their presence in certain databases.Results – There were variations in the ability of the search terms to capture the studies from individual databases, even with low-precision searches. These were mitigated by searching a combination of databases and other resources that were specific to individual topics. A combination of eight databases was important for finding literature for the included topics. Multiple database searching also mitigates the currency of content, topic and study design focus, and consistency of indexing within individual databases.Conclusion – Systematic searching for research evidence in social care requires considerable thought and development so that the search is fit for the particular purpose of supporting guidelines. This study highlights key challenges and reveals trends when utilising some commonly used databases.